Karyotype description of two Neotropical Psittacidae species: the endangered Hyacinth Macaw, Anodorhynchus hyacinthinus, and the Hawk-headed Parrot, Deroptyus accipitrinus (Psittaciformes: Aves), and its significance for conservation plans - Lunardi, Vitor de Oliveira; Francisco, Mercival Roberto; Rocha, Guaracy Tadeu [UNESP]; Goldschmidt, Beatriz; Galetti Junior, Pedro Manoel (Sociedade Brasileira de Genética, 2003)
Neotropical parrots are among the most threatened groups of birds in the world, and many species are facing extinction in a near future. At the same time, the taxonomic position of many species remains unclear. Karyotype analysis has been used to elucidate the phylogenetic status of many bird groups, also providing important information for both in situ and ex situ conservation plans. The objective of the present study was to describe for the first time the karyotypes of the endangered Hyacinth Macaw, Anodorhynchus hyacinthinus, and of the Hawk-headed Parrot, Deroptyus accipitrinus. A diploid number of 2n = 70 and a karyotype similar to the main pattern previously found for the genera Ara, Cyanopsitta, Aratinga, Propyrrhura, Pionites, Pionopsitta, Nandayus, and Guaruba were found for both species. These karyotype descriptions can be a starting point for the genetic monitoring of these two declining species.
Keywords: Avian karyotype; Anodorhynchus; Deroptyus; Psittaciformes; conservation biology; cytotaxonomy